Design and Analysis of Smart Reconstruction Plate for Wireless Monitoring of Bone Regeneration and Fracture Healing in Maxillofacial Reconstruction Applications - Shahrokh Hatefi; Farouk Smith; Kayla Auld; Stefan Van Aardt (Metrology)
In Maxillofacial Reconstruction Applications (MRA), nonunion is one of the critical complications after the reconstruction process and fracture treatment, including bone grafts and vascularized flap. Nonunion describes the failure of a fractured bone to heal and mend after an extended period. Different systems and methods have been developed to monitor bone regeneration and fracture healing during and after the treatment. However, the developed systems have limitations and are yet to be used in MRA. The proposed smart reconstruction plate is a microdevice that could be used in MRA for wireless monitoring of fracture healing by measuring the forces applied to the reconstruction plate. The device is wireless and can transmit the acquired data to a human–machine interface or an application. The designed system is small and suitable for use in MRA. The results of finite element analysis, as well as experimental verification, showed the functionality of the proposed system in measuring small changes on the surface strain of the reconstruction plate and determining the corresponding load. By using the proposed system, continuous monitoring of bone regeneration and fracture healing in oral and maxillofacial areas is possible.